GE_GERICHTE C/9087/2019 vom 30. Januar 2020 - GE Cour de justice (2020)
MAINLEVÉE DÉFINITIVE;PRESCRIPTION;AUTORITÉ FISCALE | LP.80.al1; LP.80.al2; LHID.53.al3; LHID.47.al2; LPFISC.61.al3; LPGIP.42.al1; lp.81.al1